2018
DOI: 10.1016/j.jmii.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma spp. in male infertility and its relationship with semen quality and seminal plasma components

Abstract: The infection of Ureaplasma spp. plays an important pathogenic role in male infertility. UPA has higher pathogenicity on the progressive motility and the secretary function of epididymis than UUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 28 publications
1
30
0
2
Order By: Relevance
“…Thirty‐five studies used PCR or culture to isolate specific bacteria, namely Chlamydia trachomatis , Ureaplasma spp. and Mycoplasma spp 9,19,51,52,55,60‐89 . The PCR technique identified C trachomatis in 15 studies with reported prevalence of between 0.3% and 43.3% in infertile men, which is in contrast to the culture technique where this species was not identified in any of the studies (0/20).…”
Section: Evidence Synthesismentioning
confidence: 88%
“…Thirty‐five studies used PCR or culture to isolate specific bacteria, namely Chlamydia trachomatis , Ureaplasma spp. and Mycoplasma spp 9,19,51,52,55,60‐89 . The PCR technique identified C trachomatis in 15 studies with reported prevalence of between 0.3% and 43.3% in infertile men, which is in contrast to the culture technique where this species was not identified in any of the studies (0/20).…”
Section: Evidence Synthesismentioning
confidence: 88%
“…It appears that in infertile men, U. urealyticum is more prevalent than U. parvum (Zeighami, Peerayeh, Yazdi, & Sorouri, 2009;Zhang et al, 2014;Zhou, Ma, Shi, & Liu, 2018) indicating that U. urealyticum has a clearly higher causative role in infertile men. Nevertheless, U. urealyticum is also increasingly identified to cause adverse pregnancy outcomes (Capoccia, Greub, & Baud, 2013) and both U. urealyticum and U. parvum are implicated in chorioamnionitis (Sweeney, Dando, Kallapur, & Knox, 2017).…”
Section: Ureaplasma Urealyticummentioning
confidence: 99%
“…Chlamydia trachomatis [110] and Ureaplasma sp. [111] infections are reported to affect sperm motility. Similarly, Burrello et al [112] reported that infections caused by Candida albicans, a pathogenic yeast, decreased sperm motility significantly by reducing mitochondrial membrane potential and increasing apoptosis of human spermatozoa in vitro.…”
Section: Infections and Sperm Motilitymentioning
confidence: 99%